The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1038/jhh.2008.121
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral arterial disease and isolated systolic hypertension: The ATTEST Study

Abstract: Hypertension is a risk factor for cardiovascular (CV) diseases, either coronary artery disease (CAD), peripheral artery disease (PAD) or cerebrovascular disease (CVD). The relationships between those different localizations of CV disease and the haemodynamic features of hypertension have been poorly evaluated in the past. In the ATTEST study, a geographically representative panel of 3020 general practitioners recruited 8316 consecutive patients with CV diseases (PAD, CAD or CVD, alone or in association). Blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…After deployment, a cyclic blood pressure of ±40 mmHg (i.e., pressure between 80 and 160 mmHg) was applied to the inner surface of the artery for a total of three cycles to simulate a case of isolated systolic hypertension, which has been reported to be the most frequent form of hypertension in patients suffering from PAD. 27 Blood flow computations investigated the effects of different oversizing ratios and the performances of both stents in a patient-specific artery. Following stent deployment, the deformed meshes of the artery and the stents were exported from Abaqus as open file formats (.obj) and converted to surface stl models using Solidworks 2013 (Dassault Systemes, Simulia Corp., RI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…After deployment, a cyclic blood pressure of ±40 mmHg (i.e., pressure between 80 and 160 mmHg) was applied to the inner surface of the artery for a total of three cycles to simulate a case of isolated systolic hypertension, which has been reported to be the most frequent form of hypertension in patients suffering from PAD. 27 Blood flow computations investigated the effects of different oversizing ratios and the performances of both stents in a patient-specific artery. Following stent deployment, the deformed meshes of the artery and the stents were exported from Abaqus as open file formats (.obj) and converted to surface stl models using Solidworks 2013 (Dassault Systemes, Simulia Corp., RI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In the cohort of isolated PAD, ISH was more prevalent than systolic-diastolic hypertension, as opposed to the CAD/CVD cohort in whom the latter form was more prevalent. Safar et al 16 also report that all cardiovascular risk factors increase significantly across BP classification, from normotensive to controlled hypertension, ISH and systolic-diastolic hypertension. Whatever be the antihypertensive used, the proportion of treated patients using a particular agent was between 30 and 40%.…”
mentioning
confidence: 95%
“…The antihypertensive of choice may also differ according to the dominant site of vascular disease as different drug classes are more efficient at preventing either cardiovascular or cerebrovascular complications. 15 In this issue of the Journal of Human Hypertension, Safar et al 16 report the associations between different forms of hypertension (isolated systolic hypertension (ISH), systolic-diastolic hypertension) with cardiovascular disease in different vascular territories as part of the ATTEST study. This relationship has been poorly evaluated in the past, and the ATTEST study 16 comprised 37.6% isolated PAD, 37.6% PAD with associated CAD and/or CVD and 24.8% CAD/CVD without PAD, reflecting the participant selection methods of the study (notably, two patients with PAD selected for every patient with CAD/CVD identified from general practice registers).…”
mentioning
confidence: 99%
“…Hypertension often is associated with PAD 3 ; systolic hypertension is especially highly prevalent in PAD patients, most likely because of stiffening of the large arteries. 4 Thus, antihypertensive drugs will be necessary in many PAD patients.There is no convincing evidence of superiority of one antihypertensive drug over another with respect to controlling hypertension in PAD patients or affecting their claudication distance. 5 Slightly better results are obtained by ACE inhibitors, and in some studies an increase in muscle blood flow has been shown; this was accompanied by a limited increase in walking distance (for literature review, see Reference 5 ).…”
mentioning
confidence: 99%
“…Hypertension often is associated with PAD 3 ; systolic hypertension is especially highly prevalent in PAD patients, most likely because of stiffening of the large arteries. 4 Thus, antihypertensive drugs will be necessary in many PAD patients.…”
mentioning
confidence: 99%